Learning Design of Arithmetic Sequence Material Based on PMRI with the Context of the Roof of Banyuasin Traditional House - Lasti, Nadila; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Abstract: Arithmetic sequence is one of the important materials learned in class X. However, in practice, many students face difficulties in solving problems related to this material. Therefore, this researcher aims to design a learning trajectory or Hypothetical Learning Trajectory (HLT) with the approach of Indonesian Realistic Mathematics Education (PMRI), using the context of the Banyuasin Regency traditional house. The method used was design research with the research subjects of 24 students in class X of SMK Manggala Palembang. Data collection techniques include observation, interviews and analysis of student work results on Student Worksheets (LKPD). The results of the study show that the HLT developed is effective in helping students understand the concept of arithmetic sequences in depth, understand patterns, and be able to use the nth term formula in various contextual situations. The implementation of HLT based on local context also helps students to understand the material in a more meaningful and relevant way.